Public relations w tworzeniu wizerunku przedsiębiorstw na rynku polskim - Daszkiewicz, Magdalena (Public Relations in Corporate Image Formation on the Polish Market, 2007)
The purpose of the article was to establish and evaluate the use of public relations in corporate image creation. We analyzed the situation in the field of public relations on the Polish market. The analysis was carried out on the basis of questionnaire research and in-depth interviews. The research was concerned with exploring: the place public relations take in creating corporate image, problems of organizing and planning corporate public relations, the use of marketing research in public relations activities, the role of public relations in communication with different publics. We also made an attempt to identify models of public relations used by firms operating on the Polish market.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Marketing (3); 2007; nr 1171, s. 77-85